Analysis Of Research to Determine the Effect Of Marketing On Business Activity - Berdiev J.K (Academia One Publishing, 2024)
The article reveals the importance and necessity of using digital marketing for the development of business activities in the conditions of intense competition. Also, the author's approaches to the scientific research carried out by foreign scientists on determining the impact of using digital marketing in business activities using inductive and deductive methods are presented. The main goal of this study is to give recommendations to Uzbek entrepreneurs on what and how to pay attention when organizing and conducting digital marketing activities, based on the results of research on the impact of digitization of marketing activities of business entities on business development
Keywords: entrepreneurship; digital marketing; marketing research